2003
DOI: 10.1063/1.1560562
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-etching-enhanced deep centers in n-GaN grown by metalorganic chemical-vapor deposition

Abstract: By using deep-level transient spectroscopy (DLTS), deep centers have been characterized in unintentionally doped n-GaN samples grown by metalorganic chemical-vapor deposition and subjected to inductively coupled plasma reactive ion etching. At least six DLTS traps exist in the control sample: A1 (∼0.90 eV), Ax (∼0.72 eV), B (0.61 eV), C1 (0.44 eV), D (0.25 eV), and E1 (0.17 eV), with B dominant. Then, as the etching bias-voltage increases from −50 to −150 V, trap D increases strongly and becomes dominant, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 17 publications
11
68
0
Order By: Relevance
“…It is emphasized that the capture kinetics for trap S3 is measured in the neutral region. Thus, we conclude that trap S3 in GaN on sapphire is dislocation-related defects, which is consistent with the previous report [9]. Moreover, this indicates that trap S3 is the acceptor-like defect.…”
Section: Resultssupporting
confidence: 90%
“…It is emphasized that the capture kinetics for trap S3 is measured in the neutral region. Thus, we conclude that trap S3 in GaN on sapphire is dislocation-related defects, which is consistent with the previous report [9]. Moreover, this indicates that trap S3 is the acceptor-like defect.…”
Section: Resultssupporting
confidence: 90%
“…Two defect traps are created: trap E (0.16 eV), which has been identified with the N vacancy V N [23], and trap A 2 (1.2 eV), which has an energy similar to that of trap A 1 , and may be related to the N interstitial N I . We have also found that traps E 1 , D, C, and A 1 grow under plasma-ion irradiation (not shown), indicating their defect natures [24]. Since traps E, E 1 , D, and C all grow under displacement-type irradiation and have similar energies, and since E has been positively identified with V N [23], we naturally identify each of these traps as either isolated V N (trap E), or V Nrelated complexes (traps E 1 , D, and C).…”
Section: Deep-level Transient Spectroscopy (Dlts): Trapsmentioning
confidence: 83%
“…These two traps are commonly observed in GaN on sapphire with various growth methods such as MBE and HVPE in addition to MOCVD [8][9][10][11]. From the previous possible identification [8][9][10][11], it is suggested that traps S1 (B1) and S3 (B2) might be assigned to the V N -V Ga pair and N Ga -related defect, respectively. The present result shows that these are also present in GaN grown homoepitaxially on GaN.…”
Section: Methodsmentioning
confidence: 96%